Socialization of The Implementation of Pancasila Values To Upmi Students - Taufika Hidayati; Ratna Sari Dewi; Syaipul Puad Tarigan; Khomaini Khomaini; Oktavianto Setyo Nugroho; Jenda Ingan Mahuli (International Journal Of Community Service, 2025)
Pancasila as the foundation of the Indonesian state holds a vital position in shaping the character and national identity, yet the understanding of Pancasila values among the younger generation, particularly university students, tends to deteriorate in the era of globalization. The problem faced by students at the UPMI is that their understanding of Pancasila remains normative and limited to memorizing its principles without comprehending the elaboration of values contained in each principle and how to apply them in real life. Phenomena such as intolerance, discrimination, and declining nationalism indicate that a deep understanding of the elaboration of Pancasila values has not been optimal. To address this problem, socialization activities regarding the elaboration of Pancasila values were conducted through coordination with the UPMI rectorate and the student affairs division. Implementation methods included interactive lectures, group discussions, case study presentations, and question-and-answer sessions. The material covered Pancasila as the state foundation and the urgency of understanding its value elaboration, the elaboration of values in each principle of Pancasila and their implementation in student life, as well as the role of students in preserving and disseminating Pancasila values. The results of the activity showed an increase in students' understanding of the elaboration of Pancasila values and heightened awareness to practice them in daily life, thereby forming strong student character aligned with the Indonesian national identity.